Analisis Framing Konflik Gaza di Era Informational Society (Studi Komparatif: Kompas.Com dan The Guardian) - Arsy Hafiidu Tyasepti; Alfina Dwi Maisaroh; Indria Putri Wulandari; Zulfa Alfiatus Salwa; Tasya Alifazahra; Muhammad Danu Winata (Jurnal Noken: Ilmu-Ilmu Sosial, 2026)
This study examines the framing differences in reporting the Gaza conflict by Kompas.com and The Guardian from the perspective of the informational society. The research aims to analyze how both media outlets construct the reality of the Gaza conflict and to understand the influence of their positions within the global information network on meaning-making processes. A qualitative approach with content analysis was employed to examine two news articles published on June 3, 2025, concerning the shooting of Gaza civilians during food aid distribution. The analysis was conducted using Robert Entman’s framing model, which consists of four elements: define problems, diagnose causes, make moral judgments, and treatment recommendations. The findings reveal that Kompas.com frames the Gaza conflict primarily as a humanitarian tragedy by emphasizing civilian suffering, identifying Israeli military actions as the main cause, and highlighting the need for humanitarian protection and assistance. In contrast, The Guardian frames the incident as part of broader structural issues involving aid distribution systems, blockade policies, and wider geopolitical dynamics. These differences demonstrate that media function not only as channels of information but also as producers of meaning shaped by audience characteristics, socio-political contexts, and their positions within global communication networks.